Elucidating the role of size of hydroxyl apatite particles toward the development of competent antiosteoporotic bioceramic materials: In vitro and in vivo studies. Issue 8 (3rd May 2019) - Kaur, Kulwinder; Singh, K. J.; Anand, Vikas; Bhatia, Gaurav; Singh, Amrit Pal; Kaur, Manpreet
Abstract: Osteoporosis caused by overdose of steroids is one of the major concerns for the orthopedic surgeons. Current therapeutic strategies offer limited success due to their inability to regenerate damaged bone at osteoporosis site. Therefore, there is an urgent need to develop a material having bone regeneration ability and also, ability to cure osteoporosis simultaneously. In this work, nanosized and microsized hydroxyl apatite (HAp) particles doped with europium (Eu) were prepared for diagnostic and therapeutic applications in biomedical engineering. Particles were characterized by X‐ray diffraction to confirm the formation of HAp phase and transmission electron microscopy technique has been used to explore the size of microparticle and nanoparticle. In vitro release of antibiotic drug and degradation behavior in two different pHs of phosphate buffered saline was checked. Controlled drug release behavior and conversion of degraded ions into HAp is estimated by Higuchi's and 3D diffusion model, respectively. Osteoporosis was induced in 36 female Wistar rats by administering dexamethasone once a week for four consecutive weeks. Rats were treated with different doses of nano‐HAp (25, 50, and 100 μg/kg intravenous single dose) and single dose of microsized HAp (100 μg/kg). After treatment, authors have evaluated sensitive biochemical markers of bone in serum. Continuous improvement in ultimate stiffness and Young's modulus of femur shaft of rats was observed with the increase in the dose of nano‐HAp from 25 to 100 μg/kg. Results strongly suggest that europium‐doped nano‐HAp is more effective for treating severe osteoporosis in humans. © 2019 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 107A: 1723–1735, 2019.